Age-dependent ventricular arrhythmias risk, structural and molecular remodeling in systemic arterial hypertension. (September 2017) - Scridon, Alina; Puertas, Rosa Doñate; Manati, Waheed; Fouilloux-Meugnier, Emmanuelle; Loizon, Emmanuelle; Oréa, Valérie; Chapuis, Bruno; Julien, Claude; Barrès, Christian; Tabib, Alain; Chevalier, Philippe
Highlights: Hypertensive rats present more ventricular arrhythmias than normotensive controls. In this model, left ventricular hypertrophy appears to have antiarrhythmic effects. Among the hypertensives, molecular remodeling progresses with advancing age. Kcnj11 expression was deregulated in early, but not stable ventricular hypertrophy. Myocardial energetic changes could underlie this age-dependent arrhythmogenicity. Abstract: Introduction: The left ventricular hypertrophy (LVH)-ventricular arrhythmias relationship associated with arterial hypertension and aging remains controversial. We aimed to assess the age-dependency of ventricular arrhythmias in spontaneously hypertensive rats (SHRs) and the corresponding ventricular structural and molecular remodeling. Materials and methods: Ventricular arrhythmias were quantified using 24-h radiotelemetry ECG monitoring in eight SHRs and four Wistar-Kyoto (WKY) rats at 14 (young), 24 (adult), and 48 (aging) weeks of age. Left ventricular histology and mRNA expressions of 89 proarrhythmogenic genes were assessed in six additional groups (n = 4 each) of young, adult, and aging SHRs and WKYs. Results: Regardless of their age, SHRs presented more premature ventricular contractions (PVCs) than age-matched WKYs (p < 0.01). The arrhythmogenicity peak occurred in adult SHRs; ventricular tachycardias only occurred in adult SHRs. Among the SHRs, LV thickness, interstitial fibrosis, and the number of deregulated genes increased with age. Kcnj11 expression was deregulated in adult, but not in young or aging SHRs. Discussion: This study confirms the presence of higher ventricular ectopy in SHRs than in age-matched WKYs. LVH appeared to be an adaptive, antiarrhythmic process. Myocardial energetic changes with advancing age, as reflected by Kcnj11 expression changes, could underlie this age-dependency of ventricular arrhythmias.